Sociological and ethical aspects of oncology patients’ informed consent within the legal framework of the Republic of Serbia - Vukadinović Marković, Jelena R.; Ivana,; Bogdana, (Sociološki pregled, 2025)
Informed consent reflects the personal autonomy and self-determination of a patient with respect to a proposed medical intervention, with the field of oncology presenting a particular challenge in the context of informed consent. The aim of this paper is an interdisciplinary legal, sociological, and ethical analysis of informed consent in oncology patients. The paper analyzes the conditions for the validity of informed consent from a legal perspective, the communication skills between physicians and patients, as well as ethical dilemmas related to patient autonomy within the framework of the principle of beneficence. It has been concluded that the informed consent of an oncology patient can be considered substantially valid only if, in addition to legal requirements, ethical and communication standards are also met, with the necessity of tailoring information to the patient’s individual needs.
Keywords: informed consent; oncology patient; medical sociology; medical ethics; physician–patient relationship